Hydrogel Transformed from Nanoparticles for Prevention of Tissue Injury and Treatment of Inflammatory Diseases (Adv. Mater. 16/2022). Issue 16 (21st April 2022) - Li, Zimeng; Li, Gang; Xu, Jiajia; Li, Chenwen; Han, Songling; Zhang, Chunfan; Wu, Peng; Lin, Yongyao; Wang, Chenping; Zhang, Jianxiang; Li, Xiaodong
Abstract : Functional Hydrogels In article number 2109178, Jianxiang Zhang, Xiaodong Li, and co‐workers report functional hydrogels transformed from nanoparticles in response to a physiologically and pathologically acidic microenvironment, which can be used for tissue injury protection and treatment of inflammatory diseases by triggerable and sustained delivery of therapeutic agents.